Efficacy of repetitive transcranial magnetic stimulation with different application parameters for post-stroke cognitive impairment: a systematic review - Wang, Yuhan; Wang, Linjia; Ni, Xixiu; Jiang, Minjiao; Zhao, Ling (Frontiers in Neuroscience, 2024)
Cognitive impairment is a prevalent consequence of stroke, seriously affecting recovery and quality of life while imposing substantial burdens on both patients' families and society. Repetitive transcranial magnetic stimulation (rTMS) has emerged as an effective intervention for post-stroke cognitive impairment (PSCI).However, the a lack of standardized and explicit guidelines regarding rTMS application parameters. Therefore, this study systematically evaluated the efficacy of various parameters of rTMS in treating PSCI and explored its potential mechanism.We conducted a comprehensive search across seven scientific databases, namely China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform (Wanfang), China Science and Technology Journal Database (VIP), Web of Science, PubMed, Embase, and Cochrane Library, to identify randomized controlled trials (RCTs) investigating the efficacy of rTMS for PSCI. The search encompassed the period from database creation until July 28, 2023. To evaluate the risk of bias in included studies, we employed the Cochrane recommended risk of bias assessment tool. Furthermore, we extracted relevant clinical application parameters associated with rTMS and performed comparative analyses to assess their therapeutic effects under different parameter settings.The present study included 45 RCTs involving a total of 3066 patients with PSCI.Both high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) demonstrated safety and efficacy, yet failed to exhibit significant differentiation in terms of cognitive improvement. Furthermore, intermittent theta burst stimulation (iTBS), although yielding positive results, did not surpass traditional rTMS in effectiveness.Combining HF-rTMS with LF-rTMS resulted in superior efficacy compared to single rTMS intervention. Moreover, the combination of rTMS with other cognitive therapies exhibited potential for enhanced benefits among patients.rTMS can effectively and safely enhance cognitive function, improve quality of life, and enhance activities of daily living in patients with PSCI. Furthermore, the combination of rTMS with other conventional rehabilitation methods can yield additional positive effects. However, due to insufficient evidence, an optimal parameter protocol for rTMS can not be currently recommended. Future research should prioritize orthogonal experimental design methods that incorporate multiple parameters and levels to determine the optimal parameter protocol for rTMS in PSCI.